Evaluation of a commercial quantitative Aspergillus fumigatus-specific IgM assay for the diagnosis of invasive pulmonary aspergillosis. Issue 51 (December 2017) - Yao, Yake; Zhou, Hua; Shen, Yihong; Yang, Qing; Ye, Jian; Lu, Guohua; Fu, Yiqi; Lou, Haiyan; Yu, Yunsong; Zhou, Jianying
Abstract : Abstract: Invasive pulmonary aspergillosis (IPA) is a common fungal infection with high mortality rates in immunocompromised patients. Early diagnosis of IPA is still challenging because of its nonspecific clinical symptoms and radiological presentations. To evaluate the clinical value of a commercial Aspergillus fumigates -specific IgM antibody assay in diagnosis of IPA, a multicenter prospective study was performed in 12 hospitals in Zhejiang Province, China, from January 1 to December 31, 2016. A total of 59 patients were enrolled in this study, including 30 IPA and 29 non-IPA patients. The sensitivities of IgM assay were 30.0%, 26.7%, 23.3%, and 20.0%, and the specificities were 79.3%, 86.2%, 86.2%, and 96.6% at the cutoff values of 50, 60, 70 and 80 AU/mL, respectively. The area under the curve of the IgM assay revealed by the receiver-operating characteristic analysis was 0.511 in the IPA cases. This study is the first to evaluate the clinical performance of a commercial A. fumigatus -specific IgM antibody assay that uses envelopes galactomannan extracted from A. fumigatus as the sole antigen in diagnosis of IPA. In conclusion, the A. fumigatus -specific IgM antibody assay has limited value and should not be a prior recommendation for IPA diagnosis.